Hypertension in a multi‐ethnic Asian population of Singapore - Chan, Gek Cher (J Clin Hypertens (Greenwich), 2020)
The prevalence of hypertension varies by country and region, but it remains a leading yet modifiable risk factor of cardiovascular disease. There are many factors that contribute to the burden of hypertension in Asia, a region with diverse ethnicity. It has been shown that sociodemographic variability is related to ethnic differences, thereby emphasizing the importance of hypertension screening and educating at‐risk or vulnerable groups. In this review, we describe the ethnic differences in genetic variants, dietary choice, and lifestyle habits, as well as its association with sociodemographic differences, hypertension awareness, and treatment control.